(untitled) (Research, Society and Development, 2020)
After implementation of the National Mental Health Policy, the Psychosocial Care Network was articulated as a gateway for users, improving care for patients in psychological distress. In this context is the Family Health Strategy, which proposes to build collective care practices aimed at mental health. In this context, the objective of this research is to identify mental health practices among the members of the Family Health Strategy teams of Maceió / AL. This is a study with mixed approach and quantitative and qualitative sequential transformative strategic line. As a procedure, there was a selection of a Family Health Strategy team by Primary Health Unit in each district, which are currently eight, to participate in the study. Two instruments were used for data collection: a questionnaire that identified the socio-professional profile of the participant and a semi-structured script with questions based on the guidelines recommended by the Primary Care Notebook No. 34. It was found that the professionals chosen for this study (who were 54, among nurses, doctors, dentists, nursing technicians and Community Health Agents) has been performing mental health practices, developing actions in therapeutic groups, welcoming, matriculation, individualized monitoring and, above all, supply of medicines. However, many of these professionals have a centralized management in drug treatment, and little technical knowledge of care strategies. Given this reality, it is recommended for further studies to analyze the management and quality of service provided by professionals, as well as the inclusion of users’ perception.